(untitled) - Morgan, Peter (Los Angeles, 2017)
This book contains everything students need to succeed as a business student and graduate, from essential study, presentation and leadership skills to practical advice on getting that all-important job after university.
Keywords: Kinh doanh,Business; Hướng dẫn dạy nghề,Sổ tay, sách hướng dẫn, v.v.,Vocational guidance,Handbooks, manuals, etc